Role of Microorganisms in Shaping Insect-plant Interactions - Joshi, Milind D.; Gupta, Pooja; Gaurav; Srivastava, Asutosh Kumar; Jaggi, Shikha; Hasan, Wajid; Gupta, Sheetanshu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Plants and insects have a strong interaction in the natural world, and it turns out that the little organisms known as microbes have a significant influence on how they interact. Extremely tiny living creatures called microorganisms are crucial to these interactions. Some of them work in tandem with plants to produce compounds that function as natural insect repellents. These microbes receive food from the plants in return, which allows them to survive. Furthermore, certain microbes that reside inside insects alter their behaviour and even what they eat. They may increase the likelihood that bugs will consume a certain plant or possibly lessen their resistance to the plant's defenses. Furthermore, microbes have the power to alter their environment, including the soil, by converting detritus into plant food, which influences the plants' resistance to disease and other external stresses. All of this is being studied by scientists to develop safer alternatives to conventional pesticides for protecting plants and insects. Gaining knowledge about how these microscopic organisms affect the relationships between insects and plants may help us maintain a balanced environment and healthy plants. This manuscript investigates how microorganisms influence the interactions between plants and insects. It explores how microbes aid plants in producing natural insect repellents and how they affect insect behavior and diet. The study also looks into how microorganisms impact soil health and plant resistance. Understanding these roles can lead to sustainable alternatives to conventional pesticides.